Dynamics of temporal changes of geomagnetic field secular variations - Yu.P. Sumaruk; T.P. Sumaruk (Геофизический журнал, 2016)
Time changes of the geomagnetic field secular variations, cleaned by three and eleven years running  means were studying. The years of the changes of sign secular variations and years of the changes of their velocity were found. It was shown that these years are observed at the solar activity extremeness and the secular variations jerks coincide with these years also. It made conclusion that jarks have great component due external sources